The influence of recent adhesive onlay fabrication techniques on the fracture resistance of endodontically treated premolars (An in vitro study) - Zainab Shaker Al-Taii; Inas I Al-Rawi (College of Dentistry/ University of Baghdad, 2014)
Background: Endodontically treated teeth have low resistance to fracture against occlusal forces. The strengthening effect of bonded esthetic onlay restoration on weakened tooth has been reported. This study aimed to assess the fracture resistance of endodontically treated premolars restored with composite with and without cuspal coverage by using direct and indirect techniques. Indirect technique done by CAD/CAM system (computer aided design -computer aided manufacturer) and laboratory processing. Material and methods: Forty human extracted maxillary premolars of approximately comparable sizes were divided into four groups: Group (A): Ten endodontically treated teeth directly filled with Filtek Z250xt without cuspal coverage. Group (B): Ten endodontically treated teeth prepared with onlay cavities and restored directly with Filtek Z250 XT. Group(C): Ten endodontically treated teeth prepared with onlay cavities and restored indirectly with Filtek Z250 XT. Group (D): Ten endodontically treated teeth prepared with onlay cavities and restored indirectly with Paradigm MZ100 CAD/CAM blocks. Fracture strength of the samples was measured by using universal testing machine (an axial compression test). Data were analyzed statistically by one way ANOVA test and least significant difference test, Results showed that Group A has the lowest fracture resistance value than all experimental Groups and the difference are highly significant. While Group B has a high significant fracture resistant value than the indirectly restored groups. Group C and Group D showed an approximate fracture resistant result (1.13KN and 1.07KN respectively) and the difference is statistically not significant. Conclusion All CAD/CAM composite onlay, indirect Filtek z250 XT and direct cuspal coverage survived maximum biting force for posterior single tooth, so these types of onlays provide good reinforcement in an extensive MOD cavities in premolars The mode of fracture for Group D was 90% restorable which is higher than group C (80%) restorable and group B (30%) restorable type of fracture.